Comparative characteristics of inducible NO synthase inhibitor and nitric oxide donor in endothelial dysfunction correction caused by osteoarthrosis under experimental conditions - K. S. Orel; I. V. Savitsky; I. V. Miastkivska; L. M. Zaiats (Kazimierz Wielki University, 2019)
Study have been carried out on white Wistar line rats (age - 3 months, weight - 180-220 g). According to the tasks the animals were divided into 7 groups. 1st group is intact (n = 20). 2nd group is rats, which were modeled osteoarthritis without further correction and were withdrawn from the experiment in the first stage (7th day) (n=40). 3rd group is rats, which were modeled osteoarthritis without further correction and removed from the experiment in the second stage (21st day) (n=40). 4th group is rats, in which experimental osteoarthritis was corrected with nonsteroidal anti-inflammatory drugs (NSAIDs) (Diclofenac) and aminoguanidine and removed from the experiment in the first stage (7th day) (n=20). 5th group is rats, in which experimental osteoarthritis was corrected with NSAIDs (Diclofenac) and aminoguanidine and withdrawn from the experiment in the second stage (21st day) (n=20). 6th group is rats, where experimental osteoarthritis was corrected using NSAIDs and a 7% L-arginine solution and withdrawn from the experiment in the first stage (7th day) (n=20). 7th group is rats, in which experimental osteoarthritis was corrected with NSAIDs and 7% L-arginine solution and withdrawn from the experiment in the second stage (21st day) (n=20) Animals were withdrawn from the experiment for the 7th day and the 21st day after the simulation of the pathological condition. NSAIDs (Diclofenac), aminoguanidine and L-arginine were administered from the beginning of the study. We have obtained the following results: The increase in the content of von Willebrand factor (VWF) in the animals blood proves that endothelial dysfunction is an important part of experimental osteoarthritis pathogenesis. It's revealed the tendency which directed on normalization of the endothelial dysfunction investigated marker at correction by aminoguadine as a part of complex therapy. L-arginine involvement in the complex correction in experimental osteoarthritis more pronouncedly normalized the VWF level, which indicates the endothelial function normalization. The use of nitric oxide donor is more effective in comparison with the inhibition of inducible NO synthase also in the endothelial nitric oxide synthase activity analysis.